IgA-dominant postinfectious glomerulonephritis: a case report - Moreno-Alvarado, Rodolfo; Navarro-Blackaller, Guillermo; De Leon-Pérez, Werner; Armas-Eguizabal, David; Chávez-Iñiguez, Jonathan (Frontiers in Nephrology, 2023)
Introduction Acute postinfectious glomerulonephritis (APIGN) is an immunological glomerular disease that is an important health issue in developing countries. The incidence remains high in developing countries with a male-to-female ratio of 2:1 and age predominantly above 50 years. In this case study, we present a patient with a history of Staphylococcus epidermidis infection, a past medical history of diabetes mellitus, and histopathological findings of APIGN with Immunoglobulin A (IgA) deposition. Methods A 58-year-old male presented to the emergency room with a 6-day history of severe low back pain. Three days later, the patient developed fever, chills, abdominal pain in the upper quadrant and a subsequent lower limb cellulitis. Various immunological tests, imaging studies, and kidney biopsy were performed to arrive at a diagnosis. Results Following the diagnosis and treatment of Cholangitis and Staphylococcus epidermidis, further investigation led to a diagnosis of IgA-dominant APIGN. IgA-dominant APIGN was treated with antibiotics, renin-angiotensin-aldosterone system inhibitors and steroids, and the patient was discharged from the hospital. Conclusion In developing countries, APIGN is a relatively common presentation of kidney damage due to acute kidney injury and nephritic syndrome. IgA-dominant APIGN is a rare but increasingly recognized morphological variant in which IgA is the sole or dominant immunoglobulin. This unique presentation and multidisciplinary approach for diagnosing and treating IgA-dominant APIGN need to be considered and understood by healthcare professionals to better help these patients. Further investigation is needed to understand the best treatment of this IgA-dominant APIGN presentation and its prognosis.